2004
DOI: 10.1161/01.res.0000119171.44657.45
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nrf2 in the Regulation of CD36 and Stress Protein Expression in Murine Macrophages

Abstract: Abstract-CD36 is an important scavenger receptor mediating uptake of oxidized low-density lipoproteins (oxLDLs) and plays a key role in foam cell formation and the pathogenesis of atherosclerosis. We report the first evidence that the transcription factor Nrf2 is expressed in vascular smooth muscle cells, and demonstrate that oxLDLs cause nuclear accumulation of Nrf2 in murine macrophages, resulting in the activation of genes encoding CD36 and the stress proteins A170, heme oxygenase-1 (HO-1), and peroxiredoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
296
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(324 citation statements)
references
References 51 publications
26
296
0
2
Order By: Relevance
“…Recently it has been shown that Nrf2 is a novel signaling pathway, distinct from PPARc, that also up-regulates CD36 expression in murine Mu treated with oxidized LDL. Nrf2 is a key transcription factor controlling antioxidant gene expression and that regulates antioxidant defence in Mu, implicating upregulation of CD36 in oxidative stress [43]. The recent study reporting that PPARc inhibits Nrf2-induced expression of the gene encoding thromboxane synthase in Mu, suggests that the transcriptional regulators PPARc and Nrf2 may interact [44].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that Nrf2 is a novel signaling pathway, distinct from PPARc, that also up-regulates CD36 expression in murine Mu treated with oxidized LDL. Nrf2 is a key transcription factor controlling antioxidant gene expression and that regulates antioxidant defence in Mu, implicating upregulation of CD36 in oxidative stress [43]. The recent study reporting that PPARc inhibits Nrf2-induced expression of the gene encoding thromboxane synthase in Mu, suggests that the transcriptional regulators PPARc and Nrf2 may interact [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, oxLDL-mediated activation of Nrf2 in monocyte-derived macrophages appears to play a promiscuous role by activating expression of both HO-1 and CD36 (21,126). The latter is the principal SR in foam cell formation (71). The relationship between Nrf-2 and CD36 appears to be particularly important, as Nrf-2 knockout mice on an apoE -/ -background are more resistant to atherosclerosis compared to their wild-type littermates, which is likely associated with a lower level of cholesterol influx in plaque macrophages due to decreased expression of CD36 (21).…”
Section: Ho-1 and Atheroprotective Macrophagesmentioning
confidence: 99%
“…The differences between Mox and Mhem, despite similar upregulation of HO-1, indicates that future research in this area is warranted, with particular attention to the association between heme substrate availability and the immunobiological effects of HO-1. In addition, the observation that foam cells form despite HO-1 upregulation when murine macrophages are treated with oxLDL could also be explained by the relatively low bioavailability of heme substrate in the in vitro conditions in which these studies were conducted (71). When macrophages are cultured from human monocytes treated with heme, they are resistant to lipid accumulation because the expression of the oxLDL SRs, including CD36, is significantly suppressed (53).…”
Section: Ho-1 and Atheroprotective Macrophagesmentioning
confidence: 99%
“…HNE has been shown to increase HO-1 in the cell [19,20], but the mechanism(s) has not been clearly defined. HNE is an α,β-unsaturated aldehyde that is formed from the reaction of oxygen species with arachidonate in cellular membranes during many forms of environmental stress, including exposure to cigarette smoke [9,21,22].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%